Padrões de riqueza, abundância e composição da avifauna associada às florestas ripárias do rio Branco, Roraima - Plaskievicz, Alice Caroline (2013)
The rio Branco basin covers an area with an immense variety of environments and biological diversity. Despite the ecological and biogeographical importance of the rio Branco, the ornithological research began more intensely in the last decade, and there’s little information about the species of bird found in the rio Branco forests. In this study, I provide detailed data about the composition and distribution of the birds in rio Branco. I sampled the avifauna through acoustic surveys conducted in 362 points, systematically allocated along entire river, from the source to the mouth ( ~ 550 km). Analysis of richness, abundance and distribution patterns were obtained with qualitative and quantitative data through extrapolations, cluster analysis, and identification of biogeographical barriers. On standardized surveys, recorded 297 species and 6.866 individuals, distributed in 53 families and 202 genera. Including data from sporadic observations, this number reaches 360 species, which represents a large part of the community. Using non-parametric estimators of richness, the number of bird´s species on the rio Branco forests can exceed 350. Data of total richness and abundance revealed no spatial variation along the river. Most of the species registered on standardized census were found distributed over the whole river (167 species, ~55%). However, a large number of species occurs in one region of the river: 38 (~13%) occurred only in points 1 to 4, and other 92 species (32%) exclusively in points 5 to 12. Sorting and grouping analyzes suggest strong congruence and changes in the bird community composition between savannas and forests along the rio Branco, suggesting the existence of two different avian communities. These results show that the rio Branco is very attractive for studies on distribution patterns, diversity and evolution of flooded forest’s birds, by presenting a differentiated community along the river, and on both sides, separating birds of terra firme forest from the Guiana Shield. I documented the presence and widened the distribution of species typical of the lowland, white-water river’s specialists and with isolatedpopulations in the rio Branco. Currently, the rio Branco is under threat from the Federal Government plans to use its hydropower potential, which may cause unprecedented negative effects throughout the basin.